(untitled) (Latakia University Journal -Biological Sciences Series, 2022)
Axillary seabream, Pagellus acarne (Risso, 1826), represents an important component of the Syrian waters catch. This research was conducted on 1494 individuals that were collected from the Syrian waters; by local fishing methods (Gill nets, Trammel nets) between May 2019 until the end of April 2021. The overall sex ratio (M: F) was in favour of males (1.25:1), and length-frequency distribution according to sex revealed that the males predominated at the range (13.1-16) cm, while the females were highly representative beyond 16 cm total length; which confirmed a sexual inversion already described for this Protandry species. The sex inversion occurred at 15.6 cm of total length, and the length at first sexual maturity was 12.6 cm for males and 13.2 cm for females. Gonado-somatic index GSI(%) computation and morphological monitoring of gonads maturity revealed that the spawning period of P. acarne extends from October to the end of December.